Evaluating levels of luteinizing hormone receptor dimers and oligomers - Althumairy, Duaa A., author; Roess, Deborah A., advisor; Miller, Charles W., committee member; Barisas, B. George, committee member (Colorado State University. Libraries, 2015)
Luteinizing hormone (LH) receptors are found in the female reproductive organs as well as in male reproductive organs where they play important roles in ovulation and sperm maturation, respectively. LH receptors are members of the G protein-coupled receptor (GPCR) superfamily and serve as drug targets. The role of GPCR oligomerization in receptor function is of considerable interest. Understanding the size of LH receptor clusters formed on the plasma membrane after hormone binding will lead to a better understanding of female and male reproductive functions and enhance the ability to develop better therapeutic approaches to treat diseases related to LH receptor-mediated events. Here we evaluated the oligomerization state of LH receptors using the method called polarized homo-transfer fluorescence resonance energy transfer (homo-transfer FRET) which has the ability to detect changes in the cluster size of LH receptors found in the plasma membrane. By observing increases in fluorescence anisotropy upon photobleaching of a fluorophore and analyzing the difference between the extrapolated final anisotropy and the predicted anisotropy for an immobile receptor monomer, changes in the distribution of receptor monomers, dimers and higher oligomers can be assessed. In this study different concentrations of human chorionic gonadotropin (hCG) were used to observe the effects of hormone on the oligomerization state of LH receptors. Treatment of CHO cells expressing hLHR-eYFP with increasing concentrations of hCG led to a rapid increase in formation LH receptor oligomers. In addition, this study establishes that the LH receptors may exist constitutively as dimer in control cells. These results demonstrate that polarization homo-transfer FRET is useful in evaluating the relative numbers of receptor monomers, dimers and oligomers.